Barriers and opportunities for dental school faculty research. Issue 8 (19th April 2021) - Chambers, David W.; Brady, Michelle
Abstract: Purpose/objectives: Identify barriers and opportunities regarding faculty participation in research. Methods: Sixty‐four faculty members of all ranks and days of employment completed a survey designed to reveal attitudes toward participation in research. Results: Among those responding, three‐quarters said they were actively engaged in research, and 45% of these identified no perceived barriers. Those reporting obstacles rank‐ordered 10 barriers, but no consistent patterns emerged. A factor analysis revealed three clusters of concerns: (a) school barriers, (b) personal barriers, and (c) team opportunities. A large number of comments were offered, and these tended to group by the three quantitatively identified factors. Conclusion: These findings were consistent with the view that lack of time and formal training in standardized research skills were not major impediments to scholarship. Instead, assistance in navigating administrative hurdles and participation on multiskilled teams appeared to offer the best prospect for helping faculty interested in research.